1989
DOI: 10.1111/j.1365-2621.1989.tb05134.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Dietary Oils and α‐Tocopherol Supplementation on Lipid Composition and Stability of Broiler Meat

Abstract: Broilers were fed diets containing oils of varying degrees of unsaturation, namely coconut oil, olive oil, linseed oil and partially hydrogenated soybean oil (HSBO), with and without a-tocopherol supplementation. The different oils significantly (PcO.01) affected the fatty acid composition of the neutral lipids and, to a lesser extent, the fatty acid composition of the phopholipids. Fatty acid composition, in turn, influenced the oxidative stability of the meat during refrigerated and frozen storage. Meat from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
75
0
13

Year Published

1994
1994
2010
2010

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 165 publications
(97 citation statements)
references
References 28 publications
9
75
0
13
Order By: Relevance
“…A maior proporção dos ácidos graxos está representada pelos de cadeias de 16 e 18 carbonos, conforme observado anteriormente por Asghar et al (1989) e Lin et al (1989a).…”
Section: Resultsunclassified
“…A maior proporção dos ácidos graxos está representada pelos de cadeias de 16 e 18 carbonos, conforme observado anteriormente por Asghar et al (1989) e Lin et al (1989a).…”
Section: Resultsunclassified
“…Meat rich in LNA is prone to lipid oxidation and usually contains more TBARS than does meat high in saturated or monounsaturated fats (Lin et al 1989;Asghar et al 1990). O'Keefe et al (1995) reported higher TBARS in LCn-3 enriched pre-cooked meat after 2 d of refrigeration.…”
Section: Oxidative Stability and Sensory Qualitymentioning
confidence: 99%
“…However, increasing the degree of unsaturation of the muscle membranes by dietary manipulation reduces oxidative stability in pig meat (Monahan et al 1992a) and poultry meat (Lin et al 19896). Monahan et al (1992~) observed that muscle from pigs fed on a soya-bean-oil diet (50 g oil/kg) had significantly higher c18:2/c18:1 values in the neutral and polar lipid fractions of muscle tissue and in the total fraction of adipose tissue, when compared with pigs fed on a tallow diet (50 gkg).…”
Section: Fat Compositionmentioning
confidence: 99%